Prognostic and Immunological Role of PPP1R14A as a Pan-Cancer Analysis Candidate - Wang, Zhaotao; Huang, Rihong; Wang, Haojian; Peng, Yuecheng; Fan, Yongyang; Feng, Zejia; Zeng, Zhaorong; Ji, Yunxiang; Wang, Yezhong; Lu, Jiajie (Frontiers in Genetics, 2022)
Despite emerging evidence revealing the remarkable roles of Protein Phosphatase 1 Regulatory Inhibitor Subunit 14A (PPP1R14A) in cancer tumorigenesis and progression, no pan-cancer analysis is available. A comprehensive investigation of the potential carcinogenic mechanism of PPP1R14A across 33 tumors using bioinformatic techniques is reported for the first time. PPP1R14A is down-expressed in major malignancies, there is a significant correlation between the PPP1R14A expression and the prognosis of patients. The high expression of PPP1R14A in most cases was associated with poor overall survival (OS), disease-specific survival (DSS), and progress-free interval (PFI) across patients with various malignant tumors, including adrenocortical carcinoma (ACC), bladder urothelial carcinoma (BLCA) indicated through Pan-cancer survival analysis. Receiver operating characteristic (ROC) analysis subsequently exhibited that the molecule has a high reference significance in diagnosing a variety of cancers. The frequency of PPP1R14A genetic changes including genetic mutations and copy number alterations (CNAs) in uterine carcinosarcoma reached 16.07%, and these alterations brought misfortune to the survival and prognosis of cancer patients. In addition, the methylation within the promoter region of PPP1R14A DNA was enhanced in a majority of cancers. Downregulated phosphorylation levels of phosphorylation sites including S26, T38, and others in most cases took place in several tumors, such as breast cancer, colon cancer, etc. PPP1R14A remarkably correlated with the levels of infiltrating cells and immune checkpoint genes. Our research the carcinogenic effect of PPP1R14A in different tumors is comprehensively summarized and analyzed, and provides a theoretical basis for future therapeutic and immunotherapy strategies.